2016
DOI: 10.1021/acsnano.6b01538
|View full text |Cite
|
Sign up to set email alerts
|

Nonradiative Energy Transfer from Individual CdSe/ZnS Quantum Dots to Single-Layer and Few-Layer Tin Disulfide

Abstract: The combination of zero-dimensional (0D) colloidal CdSe/ZnS quantum dots with tin disulfide (SnS2), a two-dimensional (2D)-layered metal dichalcogenide, results in 0D-2D hybrids with enhanced light absorption properties. These 0D-2D hybrids, when exposed to light, exhibit intrahybrid nonradiative energy transfer from photoexcited CdSe/ZnS quantum dots to SnS2. Using single nanocrystal spectroscopy, we find that the rate for energy transfer in 0D-2D hybrids increases with added number of SnS2 layers, a positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
118
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(121 citation statements)
references
References 39 publications
3
118
0
Order By: Relevance
“…Generally, the preparation methods can be classified into top‐down and bottom‐up methods, such as mechanical exfoliation,72, 92, 116 solvothermal method,97, 129, 140, 141 vapor deposition,69, 76, 118, 142 atomic layer deposition,126, 143 and so on. In the following context, we will focus on four methods.…”
Section: Preparation Methods and Characterizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the preparation methods can be classified into top‐down and bottom‐up methods, such as mechanical exfoliation,72, 92, 116 solvothermal method,97, 129, 140, 141 vapor deposition,69, 76, 118, 142 atomic layer deposition,126, 143 and so on. In the following context, we will focus on four methods.…”
Section: Preparation Methods and Characterizationsmentioning
confidence: 99%
“…In general, GIVMCs have been classified into two groups according to their chemical compositions: MX (SiC,89 SiS,90 GeS,91, 92 GeSe,93, 94, 95, 96 SnS,97, 98, 99 SnSe,100, 101, 102, 103, 104, 105, 106, 107, 108 SnTe,109, 110) and MX 2 (GeS 2 ,111 GeSe 2 ,112, 113, 114, 115 SnS 2 ,72, 116, 117, 118 SnSe 2 73, 119, 120, 121, 122, 123, 124, 125). In this part, some typical GIVMCs are presented in Table 1 .…”
Section: Crystal Structuresmentioning
confidence: 99%
“…The PL emission peak wavelength of 535 nm is associated with a CdSe core with $3.4 nm diameter and one monolayer (0.7 nm) thick ZnS shell. 22 Assuming a thickness of $2.3 nm for the octadecylamine ligand coating on the QD surface, the interspacing between the CdSe core (edge) and the first layer of the SnS 2 flake is thus estimated to be $3 nm, a distance at which we expect energy transfer to dominate over charge transfer. This large separation between QDs and SnS 2 , in tandem with the strong spectral overlap between QD PL and SnS 2 optical absorption, enables energy transfer from photoexcited QDs to SnS 2 , as we have recently confirmed by timeresolved single-particle PL studies of QD-SnS 2 hybrids.…”
mentioning
confidence: 99%
“…This enhanced absorption is beneficial not only for the exciton generation within the 2D material but also for the enhanced energy transfer from QDs to SnS 2 , as observed in our recent single-particle spectroscopy study, where the energy transfer rate was found to increase with the increasing number of SnS 2 layers. 22 Figure 1(a) shows a schematic of back-gated QD-fewlayer SnS 2 hybrid FET device with CdSe/ZnS QDs deposited on top of the SnS 2 channel via drop-casting from mixed solvents (hexane:octane of 9:1 volume ratio with QD solid concentration of 2.5 mg/l). The SnS 2 flake itself exhibits an optical absorption spectrum increasing sharply below $550 nm ( Figure 1(b)), which suggests a bandgap energy of $2.3 eV.…”
mentioning
confidence: 99%
See 1 more Smart Citation